2002
DOI: 10.1016/s0736-0266(01)00153-x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of wound infection in hip and knee joint replacement: results from a 20 year surveillance program

Abstract: Background. Deep wound infection (DWI) in total knee (TKA) and total hip (THA) arthroplasty has been shown to highly correlate with superficial surgical site infection (SSSI). Although several studies have reported hospital factors that predispose to SSSI, patient factors have not been clearly elucidated. Methods. All patients undergoing TKA (n = 1181) and THA (n = 1124) surgery during the period 1977–1995 at our institution were observed at the end of a 30‐day post‐operative period. Thirty‐three patients that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
221
3
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 351 publications
(244 citation statements)
references
References 28 publications
(8 reference statements)
14
221
3
6
Order By: Relevance
“…Our findings, taken together with previous studies, suggest that surgeons should think carefully before performing this elective procedure in a patient with HbA 1C C 8 or FBG C 200 mg. Although no patients in our study developed deep infection, which prevents us from evaluating the association of poor glycemic control with deep infection, previous studies reported that patients who develop superficial surgical site infection are at greater risk for deep periprosthetic joint infection [3,24,26].…”
Section: Discussionmentioning
confidence: 62%
“…Our findings, taken together with previous studies, suggest that surgeons should think carefully before performing this elective procedure in a patient with HbA 1C C 8 or FBG C 200 mg. Although no patients in our study developed deep infection, which prevents us from evaluating the association of poor glycemic control with deep infection, previous studies reported that patients who develop superficial surgical site infection are at greater risk for deep periprosthetic joint infection [3,24,26].…”
Section: Discussionmentioning
confidence: 62%
“…Saleh et al [8] reported 19 out of the 33 (58%) study subjects with superficial surgical site infection developed deep wound infection. Of the preoperative, intraoperative, and postoperative factors examined, only hematoma formation and days of postoperative drainage were noteworthy predictors of superficial surgical site infection.…”
Section: Discussionmentioning
confidence: 99%
“…One study suggests deep wound infection after total knee and hip arthroplasty correlates with superficial surgical site infection [8]. Saleh et al [8] reported 19 out of the 33 (58%) study subjects with superficial surgical site infection developed deep wound infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies adhere to these criteria [3,30,35,37]. This requires 12-month followup and we were able to classify cases into deep and superficial infection based on the Centers for Disease Control and Prevention criteria.…”
Section: Discussionmentioning
confidence: 99%